2022
DOI: 10.3390/jcm11216352
|View full text |Cite
|
Sign up to set email alerts
|

Serum Inflammatory Markers and Their Associations with the Integrity of the Cingulum Bundle in Schizophrenia, from Prodromal Stages to Chronic Psychosis

Abstract: Peripheral cytokines may affect the brain through chronic activation of microglia and, as a result, can potentially lead to decreased integrity of white matter of cingulum bundle (CB). Therefore, the aim of the study was to analyze the relationships between peripheral inflammatory markers and the integrity of the CB in various states: from healthy controls, through prodromal states and first-episode psychosis, to long-term schizophrenia. The integrity of the CB was measured using diffusion tensor imaging. We a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 57 publications
0
4
0
1
Order By: Relevance
“…Our previous study showed that the levels of some IM parameters ([ 15 ], supplementary table) and some DTI parameters of SLF and ILF (data not shown) are correlated with age and BMI. We also found some associations between IM and smoking, disease duration, exacerbations, types, and doses (chlorpromazine equivalent) of antipsychotics ([ 15 ], supplementary table).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Our previous study showed that the levels of some IM parameters ([ 15 ], supplementary table) and some DTI parameters of SLF and ILF (data not shown) are correlated with age and BMI. We also found some associations between IM and smoking, disease duration, exacerbations, types, and doses (chlorpromazine equivalent) of antipsychotics ([ 15 ], supplementary table).…”
Section: Resultsmentioning
confidence: 99%
“…Our previous study showed that the levels of some IM parameters ([ 15 ], supplementary table) and some DTI parameters of SLF and ILF (data not shown) are correlated with age and BMI. We also found some associations between IM and smoking, disease duration, exacerbations, types, and doses (chlorpromazine equivalent) of antipsychotics ([ 15 ], supplementary table). Therefore, for each analyzed IM and DTI parameter, an additional multiple linear regression analysis was performed in two variants: (a) taking into account age and BMI (in every study group); and (b) taking into account age, BMI, smoking, disease duration, exacerbations, types, and doses of antipsychotics (in UHR (without smoking), FEP, and SCH).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Однако результаты исследований достаточно противоречивы. Не удалось, например, выявить связи между повышением концентраций таких цитокинов, как CRP, IL-6, IL-8, IL-10, TNF-α и IFN-γ, в плазме крови пациентов и структурой белого вещества поясного пучка в их мозге [92]. Этот тракт, связывающий лобную, теменную и височную кору, является по данным ДТТ одной из областей с наиболее выраженными нарушениями структуры миелина как у больных шизофренией, так и у лиц с высоким риском психоза [93].…”
Section: нейровоспаление при шизофрении и иммунокомпетентность проген...unclassified